2020
DOI: 10.3390/catal10010106
|View full text |Cite
|
Sign up to set email alerts
|

A Cellulose Electrolysis Cell with Metal-Free Carbon Electrodes

Abstract: Biomass raw materials, including agricultural residues, collected weeds, and wood chips, are important feedstocks for hydrogen production. Numerous attempts have been made to electrolyze biomass directly or indirectly to hydrogen because these processes allow for the production of hydrogen with less power consumption than water electrolysis. However, expensive metal-based electrocatalysts are needed, especially for the cathode reaction, in the electrolysis cells. Results from the present study demonstrate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Additionally, when the conditions in the cathodic chamber is appropriately adjusted (that is, O 2 dissolved in the catholyte is removed), the photoelectrochemical cell can generate hydrogen from the biomass resources rather than the electricity. [36] The intermediate products of the PEC cellulose decomposition were determined using high-performance liquid chromatography (HPLC) [11] as summarized in Figure 6a. The carbonyl hydrocarbon chains, such as gluconic acid, oxalic acid, acetic acid, and formic acid, were observed as intermediate products dissolved in the liquid phase after the PEC reaction ( Figure S5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, when the conditions in the cathodic chamber is appropriately adjusted (that is, O 2 dissolved in the catholyte is removed), the photoelectrochemical cell can generate hydrogen from the biomass resources rather than the electricity. [36] The intermediate products of the PEC cellulose decomposition were determined using high-performance liquid chromatography (HPLC) [11] as summarized in Figure 6a. The carbonyl hydrocarbon chains, such as gluconic acid, oxalic acid, acetic acid, and formic acid, were observed as intermediate products dissolved in the liquid phase after the PEC reaction ( Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it can be concluded that the present PFC could successfully convert the energy of light and biomass (cellulose) into electricity. Additionally, when the conditions in the cathodic chamber is appropriately adjusted (that is, O 2 dissolved in the catholyte is removed), the photoelectrochemical cell can generate hydrogen from the biomass resources rather than the electricity [36] …”
Section: Resultsmentioning
confidence: 99%
“…Present as the most and second abundant source of biomass, cellulose, and lignin are considered the most attractive proton and carbon source due to their availability and low-cost. Biomass electrolysis of these raw feedstocks, lignin, [271][272][273][274][275] and cellulose [276,277] has therefore also been studied. Similar to methanol and ethanol electrolysis, the primary focus on lignin and cellulose electrolysis is H 2 production with less electricity consumption.…”
Section: Ethanolmentioning
confidence: 99%
“…Furthermore, the electrolysis temperature is a key factor for LAWE. At low temperatures, the conversion rate of lignin and the rate of hydrogen evolution reaction (HER) is generally low (Caravaca et al, 2019;Li et al, 2020). But both of them can be promoted evidently when the temperature is increased from ambient temperature to about 100 °C (Zirbes and Quadri, 2020).…”
Section: Introductionmentioning
confidence: 99%